Multi-omics revealed the effects of rumen-protected methionine on the nutrient profile of milk in dairy cows. (November 2021) - Gu, Fengfei; Liang, Shuling; Zhu, Senlin; Liu, Jianxin; Sun, Hui-Zeng
Graphical abstract: Highlights: Uncovered the changes in milk metabolome and rumen microbiome after RPM addition. α-ketoglutaric is the key improved functional metabolite after RPM addition. Acetate-producing bacteria are significantly changed after RPM addition. Multi-omics revealed the association between the changed metabolites and bacteria. Abstract: Cow's milk is a highly-nutritious dairy product part of human diet worldwide. Rumen-protected methionine (RPM) is widely used to improve lactation performance of dairy cows, but understanding of the effects of RPM on milk nutrients composition are still limited. In this study, twenty mid-lactating dairy cows were supplemented with 20 gm/day RPM for 8 weeks to investigate the responses of milk nutritional composition to RPM. Metabolomics was applied for analyzing milk metabolites and 16S rRNA gene sequencing was used for analysis of rumen microbial composition. Milk fat content and yield were significantly increased after RPM supplementation. Totally 443 compounds belonging to 15 classes were identified, among which 15 metabolites were significantly changed. The functional nutrient α-ketoglutaric acid were significantly increased in the milk after RPM supplementation. We found 48 significantly differing bacterial genera in the rumen after supplementing RPM. Multi-omics integrated analysis revealed the higher abundance of Acetobacter, unclassified_f_Lachnospiraceae and Saccharofermentan contributed to the improved milk fat. In addition, the enriched abundance of Thermoactinomyces, Asteroleplasma, and Saccharofermentan showed positive correlations with higher α-ketoglutaric acid of milk. Our results uncover the metabolomic fingerprint and the key functional metabolites in the milk after supplementing RPM in dairy cows, as well as the key rumen bacteria associated with them. These findings provide novel insights into the development of functional dairy products that enriched the functional nutrient α-ketoglutaric acid or high milk fat.